KEBERADAAN BAKTERI Escherichia coli PADA AIR KOLAM RENANG UMUM - Indah Wahyuningtias; Bambang Sunarko; Iva Rustanti EW (Poltekkes Kemenkes Surabaya, 2019)
One indicator of swimming pool water pollution is the presence of Escherichia coli bacteria. Factors can caused the presence of Escherichia coli in pool water are the levels of residual chlorine, the visitors who dispose of metabolic waste (sweat, urine) in pool water and disinfection of pool that were not done properly. This study analyzes the quality of swimming pool water seen from the presence of Escherichia coli in public pool water. This study was an observational analytic that use a cross sectional research design. The sample used were public swimming pool located in the Sukodono Health Center working area with total of pools were 10, and with Fisher's exact test. The results showed that main factor affecting the presence of Escherichia coli in pool water was residual chlorine content with a p-value of 0.019 which means that there was a difference number of Escherichia coli in swimming pools containing residual chlorine and in pool water that didn’t contain residual chlorine.This study concluded that there were differences in the number of Escherichia coli bacteria in pool water containing residual chlorine and in pool water that did not contain residual chlorine. To keep the remaining chlorine in pool water in accordance with Permenkes No. 32 of 2017, pool managers should routinely check the remaining chlorine and do chlorination regularly. Keywords: Escherichia coli, residual chlor, swimming pool